What is a Conceptual Framework for Financial Reporting?. (2nd September 2018) - Dennis, Ian
ABSTRACT: Despite more than forty years of exploration into constructing a conceptual framework (CF) for financial reporting the question 'What is a CF?' has not been adequately answered. The result is that those who construct CFs are not guided by a clear concept of a CF and communication about CFs is undermined by differences in understanding what it is. There has been a failure to undertake conceptual enquiry into the nature of a CF or into the expressions used in describing it. This paper addresses this failure by undertaking such a conceptual enquiry. Existing explanations of CFs are examined and found to be inadequate. What is wanted from a CF is identified and explained and this is used to prescribe what should be understood by the expression 'conceptual framework'. A new characterisation of CFs is given that should assist any future construction of new CFs. Problems that may be faced by those who seek to construct a CF are identified.